Marketing Strategy Management for Early Childhood Education RA Al Wardah North Sumatra - Yuning Eka Rahma Wati (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
Marketing management can be used as a mechanism for explaining and rationalizing a program's offerings with various advantages, both in terms of inputs (inputs), processes, products (outcomes), outputs (outputs), and graduates (effects). In addition, promotion can also be used to convey public accountability regarding the educational process and results that have been implemented and developed by the educational institution concerned. The formulation of this research is how the education marketing management process in RA Al Wardah North Sumatra, what are the targets to be achieved by RA Al Wardah North Sumatra with the implementation of marketing management, what is faced by RA Al Wardah North Sumatra in the performance of marketing management. The research was conducted in RA Al Wardah, North Sumatra, and the data source for this study was the principal. This study uses qualitative research methods. Observation, interviews, and documentation do data collection. Data analysis is done through data reduction, data presentation, and conclusion. Based on the study results, it can be concluded that marketing management at RA Al Wardah, North Sumatra is running very well and following the times. The marketing strategy by RA Al Wardah North Sumatra is to continuously improve the quality of educational services, has the characteristic of educating children to be pious and independent, holding various extracurricular activities outside school hours, and holding multiple competitions.